Analisis Kepribadian Tokoh Kasminta dalam Novel Donyane Wong Culika Karya Suparto Brata - Firmansyah, Ardi; Prastowo, Galang; Rakhmani, Futya (STKIP PGRI Ponorogo Press, 2025)
This research was conducted with the opinion that literary works in the form of novels are a reflection of life described through the experiences of the characters in the story. This research aims to analyze the personality structure of the character Kasminta in the novel with the title Donyane Wong Culika by Suparto Brata. The approach used in the research is literary psychology with Sigmund Freud's psychoanalysis theory, especially the personality structure. the data source of this research is a modern Javanese-language novel with the title Donyane Wong Culika by Suparto Brata published in 2004, with dialog or narrative quotes as the main data. The result of this research is the discovery of Freud's three types of personality structure in Kasminta's character, namely 1) Id which rejects discomfort; 2) Ego in the form of decision making based on Id's encouragement; 3) Superego in the form of two subsystems of Superego itself, namely conscience in the form of awareness of mistakes made in the past and ego ideal that can distinguish good and bad behavior.